2018
DOI: 10.3892/mmr.2018.9577
|View full text |Cite
|
Sign up to set email alerts
|

Roles of fatty acid metabolism in tumourigenesis: Beyond providing nutrition (Review)

Abstract: Fatty acid (FA) metabolism, including the uptake, de novo synthesis and oxidation of FAs, is critical for the survival, proliferation, differentiation and metastasis of cancer cells. Several bodies of evidence have confirmed the metabolic reprogramming of FAs that occurs during cancer development. The present review aimed to evaluate FAs in terms of how the hallmarks of cancer are gradually established in tumourigenesis and tumour progression, and consider the auxo-action and exact mechanisms of FA metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 99 publications
0
18
0
Order By: Relevance
“…Cancer cell proliferation also requires the duplication of cellular macromolecular components during each cell division, making lipid metabolism a principal physiological pathway for maintaining cell architecture, growth and physiological homeostasis [86,87,88,89]. The link between glycolysis and the lipid metabolism could be evident by the fact that a portion of acetyl-CoA could be carboxylated into malonyl-CoA by acetyl-CoA carboxylase (ACACA), the primary rate-limiting enzyme of the de novo fatty acid biosynthesis pathway, followed by the condensation of acetyl-CoA and malonyl-CoA by fatty acid synthase (FASN) to produce saturated fatty acids (FAs).…”
Section: Development Of Anti-cancer Scheme By Targeting Distinct Mmentioning
confidence: 99%
“…Cancer cell proliferation also requires the duplication of cellular macromolecular components during each cell division, making lipid metabolism a principal physiological pathway for maintaining cell architecture, growth and physiological homeostasis [86,87,88,89]. The link between glycolysis and the lipid metabolism could be evident by the fact that a portion of acetyl-CoA could be carboxylated into malonyl-CoA by acetyl-CoA carboxylase (ACACA), the primary rate-limiting enzyme of the de novo fatty acid biosynthesis pathway, followed by the condensation of acetyl-CoA and malonyl-CoA by fatty acid synthase (FASN) to produce saturated fatty acids (FAs).…”
Section: Development Of Anti-cancer Scheme By Targeting Distinct Mmentioning
confidence: 99%
“…Lipids which mainly include fatty acids and cholesterol are vital sources of energy metabolism in the human body [33]. Studies suggested that to meet the needs of biosynthesis during high levels of proliferation, the reprogramming of fatty acid (FA) metabolism becomes essential in cancer cells [34]. e abnormal fatty acid metabolism affects numerous vital cellular processes including cell growth, proliferation, and survival [17,35], thus playing a crucial role in cancer development and progression [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…SREBP1 is linked to fatty acid and phospholipid synthesis, whiles SREBP2 is linked to cholesterol synthesis through its regulation of 3-hydroxy-3- The multifunctional polypeptide, fatty-acid synthase (FASN), catalyzes the last step in de novo biogenesis of fatty acids [81]. FASN produces saturated fatty acids sequentially by adding seven malonyl-CoA molecules to one acetyl-CoA to form the 16-carbon palmitate [82,83]. FASN has been studied in various cancers, these studies report FASN overexpression correlates with tumor progression [81,[84][85][86][87].…”
Section: Mechanisms Of Fatty Acid Metabolic Reprogrammingmentioning
confidence: 99%